2022
DOI: 10.1097/ta.0000000000003835
|View full text |Cite
|
Sign up to set email alerts
|

When is enough enough? Odds of survival by unit transfused

Abstract: Transfusion is lifesaving. The Red Cross blood shortage in Jan 2022 threatened the immediate availability of blood. When blood is scarce, who benefits most from a unit? At 11U PRBC mortality = survival; 16U mortality > survival; >36U mortality is expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 33 publications
1
39
1
Order By: Relevance
“…The reported mortality rates for trauma patients receiving UMT ranged from 29% to 69%. 6,7,13,14,[26][27][28][29][30][31][32][33][34][35] Most studies examining UMT in trauma patients did not appear to support a cutoff value of blood products based on mortality rates, 6,7,13,14,[26][27][28][29][30][31][33][34][35] although there was a trend toward increased mortality as the number of blood products transfused increased. 6,7,13,32 Several studies have demonstrated that trauma patients who receive >35 to 40 units of RBC significantly increase mortality rates, 7,32,38 with one suggesting 100% mortality after 67 units RBC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reported mortality rates for trauma patients receiving UMT ranged from 29% to 69%. 6,7,13,14,[26][27][28][29][30][31][32][33][34][35] Most studies examining UMT in trauma patients did not appear to support a cutoff value of blood products based on mortality rates, 6,7,13,14,[26][27][28][29][30][31][33][34][35] although there was a trend toward increased mortality as the number of blood products transfused increased. 6,7,13,32 Several studies have demonstrated that trauma patients who receive >35 to 40 units of RBC significantly increase mortality rates, 7,32,38 with one suggesting 100% mortality after 67 units RBC.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,13,14,[26][27][28][29][30][31][32][33][34][35] Most studies examining UMT in trauma patients did not appear to support a cutoff value of blood products based on mortality rates, 6,7,13,14,[26][27][28][29][30][31][33][34][35] although there was a trend toward increased mortality as the number of blood products transfused increased. 6,7,13,32 Several studies have demonstrated that trauma patients who receive >35 to 40 units of RBC significantly increase mortality rates, 7,32,38 with one suggesting 100% mortality after 67 units RBC. 32 The largest study-to-date was performed by Gallastegi et al, which analyzed UMT recipients found in the national trauma database, did not demonstrate a direct correlation between the volume of blood transfused at either 4 or 24 hours and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations